Supply chain environmental and social sustainability practice diffusion: Bibliometrics, content analysis and conceptual framework - Pimenta, Handson Claudio Dias; Ball, Peter; Salonitis, Konstantinos (Wiley, 2021)
The purpose of this paper is to uncover how environmental and social sustainability practices are diffused across the supply chain tiers through supplier development initiatives. In particular, the work seeks to uncover the initiatives developed directly or indirectly by manufacturing firms and the factors that enhance them. A systematic literature review is used to examine the breadth of the sustainable supply chain literature. The papers obtained are screened and analysed using established procedures to produce bibliometric and thematic analyses. The findings show the evolution of this young field around key research groups with few papers looking beyond focal firms to immediate suppliers and even fewer examining multiple tiers. Whilst numerous organisational factors are identified, few works consider most of them together and none capture their interrelationships at such breadth. Within this field lacking in theory, the originality of the work is the assembly of environmental and social practices into an integrated framework for their diffusion across supply chain tiers in the design and implementation of supplier development initiatives. There is recognition of where in the supply chain these practices are applied. The implications of this research are a framework around which supply chain diffusion theory can be tested and subsequent potential for its deployment in business to guide sustainable practice adoption.
Keywords: Sustainable supply chain management; supplier sustainability development; stakeholder engagement; environmental and social sustainability practices